Pengembangan Learning Management System dengan Framework Laravel dan Tailwind CSS - Mardiana, Iklima; Wahyudin; Junaeti, Enjun (MULTINETICS, 2024)
Education today is increasingly faced with the challenge of integrating technology in the learning process to improve quality and accessibility. In this context, the development of Learning Management System (LMS) using Laravel framework and Tailwind CSS becomes an interesting solution. Therefore, the purpose of this research is to develop a Learning Management System using Laravel framework and Tailwind CSS in its development, which is expected to create a technological solution that can improve the quality of learning and provide wider accessibility to learning resources. A research and development (R&D) approach is used in this study, which involves problem identification and needs analysis, solution concept design, LMS media development, testing, and media validation. The evaluation results showed significant validation, with 81.9% validation by lecturers and 100% by teachers, as well as an average validation of 90.95%, positioning the LMS in the "excellent" category and feasible to use as an online learning platform. Thus, the development of LMS using Laravel framework and Tailwind CSS has proven to be efficient and useful, providing relevant solutions to the quality and accessibility of learning.